The Effect of Kinder Therapy on Improvement of Teachers’ Interaction of Toddlers’ Problem Behavior (Medico Legal Update, 2019)
The purpose of this study was to develop kinder teacher treatment play therapy for kindergarten children.SPSS version 22.0 for Windows was used for data analysis to develop kinder teacher treatment play therapyfor kindergarten children. Among nonparametric statistical methods, the Mann-Whitney U Test and theWilcoxon Singed-Rank Test were conducted. The results of this study are summarized as follows. Kindertherapy had a positive effect on the improvement of teachers’ interaction. The difference between the pretestand the posttest showed that their positive and permissive interactions improved and that their punitive anddetached interactions decreased. This study shows that it is difficult to generalize the result by participationby a small number of people, but it is proved that kinder therapy is effective in improving teacher interactionability and reducing kinder’s problem behavior in a childcare center.